EVALUASI USABILITY WEBSITE MITRA LAUNDRY SCLEAN DENGAN MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Zizky Yuningsih; Sudirman; Arfan Yunus (STMIK KHARISMA Makassar, 2022)
SCLEAN (Smart Cleaning) is a mobile device made to connect laundry with laundry service users. Mobile SCLEAN devices are also designed with two sides, namely from the side of the laundry service user using the mobile version and from the laundry service provider side using the Website version. The laundry admin website is a very important component in connecting laundry and laundry service users. Researchers want to conduct research that aims to evaluate the performance of the SClean laundry partner admin website and are expected to provide suggestions that are used as a reference for the improvement and development of the SClean laundry partner website by NuCom. By using the System Usability Scale method, it shows that the evaluation results have a score of 59, the value is included in the marginal category in grade D with an OK rating and website improvement recommendations for improving service features on the website and optimizing performance on the website.